PROSES ASESMEN BERBASIS KOMPETENSI BAGI COMMUNITYWORKER DI LEMBAGA SERTIFIKASI PROFESI FASILITATOR PEMBERDAYAAN MASYARAKAT (LSP FPM) - Sidqiyah, Chamiyatus; Rahayu, Ety (UI Scholars Hub, 2020)
Community workers have roles and functions in empowering communities, especially those who are disadvantaged, poor, or lacking access to increased prosperity. Since 2000, the Indonesian Government has developed poverty alleviation programmes with community empowerment approaches and many Community Worker personnel recruited as PNPM Mandiri facilitators in rural and urban areas in various regions in Indonesia. Currently, the number of Community workers has reached tens of thousands but the future of this profession has a problem because the policy and law labor regulation demands that every profession that works should be able to demonstrate its competence through assessment based competency with national recognized competency standards and expressed in the form of competency certificate. Apart from the pros and cons of competency assessment ideas for Community workers, researchers think this still needs to be reviewed and developed because competency problems are issues of professional responsibility and Community Workers will experience challenges in the global future. Research on the process of competency assessment for Community workers at LSP FPM is aimed at the process of assessment processes done and the results, and hopefully can be contributed both academically and practically for the efforts of the development Community Worker profession.